2016
DOI: 10.1016/j.ijhydene.2016.09.045
|View full text |Cite
|
Sign up to set email alerts
|

Development of improved nickel catalysts for sorption enhanced CO2 methanation

Abstract: a b s t r a c tSorption enhanced CO 2 methanation is a complex process in which the key challenge lies in the combined optimization of the catalyst activity and water adsorption properties of the zeolite support. In the present work, improved nickel-based catalysts with an enhanced water uptake capacity were designed and catalytically investigated. Two different zeolite frameworks were considered as supports for nanostructured Ni, and studied with defined operation parameters. 5Ni/13X shows significantly incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 28 publications
4
59
0
1
Order By: Relevance
“…Supported Ni catalysts are the most widely investigated materials for CO 2 methanation due to their high efficiency in CH 4 production and low cost [75][76][77][78][79][80][81][82][83][84][85][86][87][88][89]. A lot of supports have been investigated for Ni catalysts since, as is well known, the catalytic performance strongly depends upon the nature and properties of the support.…”
Section: Nickel-based Catalystsmentioning
confidence: 99%
“…Supported Ni catalysts are the most widely investigated materials for CO 2 methanation due to their high efficiency in CH 4 production and low cost [75][76][77][78][79][80][81][82][83][84][85][86][87][88][89]. A lot of supports have been investigated for Ni catalysts since, as is well known, the catalytic performance strongly depends upon the nature and properties of the support.…”
Section: Nickel-based Catalystsmentioning
confidence: 99%
“…Thus, a sorption catalyst typically consists of the active catalyst (consisting, e.g., of transition metal nanoparticles), which is embedded in a sorbent with a high selective affinity for the product. Recent studies have demonstrated this concept with the hydrogenation of CO 2 to methane left CO 2 + 4 H 2 CH 4 + 2 H 2 O Δ H 0 = 165 kJ mol 1 …”
Section: Introductionmentioning
confidence: 99%
“…Reaction is ideal to explain the principle of sorption enhancement: the product methane is hardly adsorbed on the catalyst as compared to water. Sorption enhancement is thus achieved by the removal of water from the reaction sites …”
Section: Introductionmentioning
confidence: 99%
“…4. Atmospheric pressure is assumed here from the authors, since recent developments in catalysis showed methane yields up to 100% already at atmospheric pressure (Delmelle et al, 2016). By this, the compression energy is also significantly lower since only methane must be compressed to natural gas grid pressure instead of CO2 and H2, which needs five times more compression energy and a H2 suitable technology.…”
Section: General Technical Considerations For the Applied Modelmentioning
confidence: 99%
“…The subsequent conversion of this H2 with CO2 is assumed to take place at ambient pressure and 300°C, since these conditions are technically feasible to reach 100% CO2 conversion with stateof-the-art for common nickel catalysts (Delmelle et al, 2016). The authors furthermore assumed for this case study that compression of one unit of CH4 is more efficient and more economic than compressing 5 units of reactant gasses under stoichiometric conditions, i.e., 4 units H2 and one unit of CO2 and therefore, compression on gas grid conditions takes place after methanation.…”
Section: Energetic Consideration For H 2 Production By Ael and Its Comentioning
confidence: 99%